ANALISIS PENGARUH CAMPURAN PUPUK UREA TERHADAP KUAT GESER TANAH LEMPUNG LUNAK DENGAN UJI TRIAXIAL - Sutejo, Yulindasari; Dewi, Ratna; Haryadi, Dwi; Kurniawan, Reffanda (Jurusan Teknik Sipil & Perencanaan Fakultas Teknik Universitas Sriwijaya, 2015)
The soilÂ plays an important roleÂ inÂ a construction site. One type is the soft clay soil that has a value compressibility and high water levels so low soil shear strength that reduce the bearing capacity of the soil. In this study conducted by the method of soil improvement, soilÂ stabilization using a mixture of ureaÂ fertilizer with percentage of 5 %,Â 10 %,Â and 15 % with a treatment period of 3 , 7,Â and 14 days with Triaxial test. Soft clay soil samples taken in the area around UNSRI, Inderalaya, OI, South Sumatra. The test results of soil properties, w 35.20 %; 2.53 Gs; PL 21.14 %; LL 42 % and IP 20.86 %. According to the USCS, the soil categorized CL, while according to AASHTO, the soil is categorized class A-7-6. Results of Triaxial testing , the value of cohesion (c) 5 % maximum on the addition of ureaÂ fertilizer (14 days) is 1.138 kg /cm2 . While the value of shear angle (f) and shear strength (Ï) maximum on the addition of 15 % ureaÂ fertilizer (3 days) of 26,42o and 3.93 kg /cm2 .Key Words : UreaÂ Fertilizer, Shear Strength, Triaxial, Soft Clay